Effect of Recirculation Channel on Aerodynamic Performance of a Single-Stage Transonic Axial Compressor - Dinh, Cong-Truong (Old Journal, 2020)
This paper investigates the effects of recirculation channel on the performance of a single-stage transonic axial compressor, NASA Stage 37, such as pressure ratio, adiabatic efficiency, and operating range. Numerical analysis was conducted by solving three-dimensional steady Reynolds-averaged Navier-Stokes equations with the k-epsilon turbulence model. The recirculation channel bled the high-pressure flow from the stator shroud domain and injected it into the rotor tip clearance domain to increase the aerodynamic performance. The locations and widths of the injection and bleed ports were selected as parameters for the study to find the optimum recirculation channel design. The results indicated that, in general, the stall margin and operating range were significantly extended by from 0.45% to 2.38%, and from 3.72% to 12.7%, respectively, as compared to the performance of the smooth case without recirculation channel.